Aspek-Aspek Psikologis dalam Budaya Carok - Barokatul Asiyah; Darmawan Muttaqin (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
The Madurese community has a very unique and distinctive culture, one of which is Carok. Carok culture is an attempt to kill men against men as a result of lowered self-esteem. So far, carok has always been synonymous with things that are considered rude and cruel. It also creates a bad stigma against the Madurese community. Non-Maduran people only look globally without understanding more deeply the meanings contained in carok. The purpose of this article is to provide a study of carok culture from a psychological perspective. This study is expected to help understand and explain the carok culture not only as a culture, but also the psychological side of the Madurese community in doing carok. In addition, it is also hoped that it can explain to readers and the wider community that what is contained in carok culture is not only something related to negative behaviour. Carok is one way to solve problems that are full of meaning. In carok there is high collective self-esteem, social prestige, and consensus. Referring to the results of research and literature, psychological approaches can be applied in developing knowledge, insight, and understanding about carok culture. The theoretical and practical implications can be discussed further.